SAMPLING AND ANALYSISING OF DISSOLVED OXYGEN IN WATER SAMPLES COLLECTED AT SUNDARAPURAM IN COIMBATORE DISTRICT - Kumar, K, Senthil; kumar, P, Selva (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Maintenance of dissolved oxygen at saturated level will help the growth and reproduction of normal population of fish and other aquatic organisms1,2. Due to increase of industries, it is necessary to monitor the DO level of water resources. This will help us to understand the present condition of water at various resources that are connected to the industries. In this study the water is collected from various resources around Sundarapuram in coimbatore district and they were subjected to dissolved oxygen study. The DO results of various samples were compared with DO of demineralised water which is taken as reference. Parameters such as temperature, hardness and aeration time that will affect the saturation level of DO are also discussed 6,7,8.Â